The Roles and Use of Law in Green Criminology - Matthew Hall (International Journal for Crime, Justice and Social Democracy, 2014)
This paper examines how law and legal analysis fit within the broader green criminological project. By demonstrating how legal analysis in various forms can cast significant light on key green criminological questions, the paper seeks to address the concern that green criminology – with its preponderance of ‘deep green’ viewpoints and focus on social harms which are not proscribed by formal law – precludes the application of legalistic values such as certainty and consistency. Ultimately, the goal of the paper is to demonstrate how, despite the novel challenges to the legal scholar presented by green criminology, the incorporation of a more legalistic perspective within an interdisciplinary exercise is not only desirable for green criminology but is in fact vital if the field is to realise its ambitions as a force for environmental good.